2021
DOI: 10.3390/healthcare9060701
|View full text |Cite
|
Sign up to set email alerts
|

Pediatricians’ Compliance to the Clinical Management Guidelines for Community-Acquired Pneumonia in Infants and Young Children in Pakistan

Abstract: Community-acquired pneumonia (CAP) is among the most commonly prevailing acute infections in children that may require hospitalization. Inconsistencies among suggested care and actual management practices are usually observed, which raises the need to assess local clinical practices. The current study was conducted to evaluate pediatricians’ compliance with the standard clinical practice guidelines and their antibiotic-prescribing behavior for the management of CAP in children. Methods: A descriptive cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
1
1
Order By: Relevance
“…Healthcare practitioners could play a role in educating the population in order to reduce the inappropriate use of antibiotics. In this study, the preferred method of antibiotics was IV, in contradiction to the findings of another study in which physicians chose oral antibiotics over IV or IM antibiotics [ 29 ]. It is documented that physicians believed broad-spectrum or new antibiotics to be more effective, which is an impression that is frequently reinforced by pharmaceutical organizations’ advertising.…”
Section: Discussioncontrasting
confidence: 73%
“…Healthcare practitioners could play a role in educating the population in order to reduce the inappropriate use of antibiotics. In this study, the preferred method of antibiotics was IV, in contradiction to the findings of another study in which physicians chose oral antibiotics over IV or IM antibiotics [ 29 ]. It is documented that physicians believed broad-spectrum or new antibiotics to be more effective, which is an impression that is frequently reinforced by pharmaceutical organizations’ advertising.…”
Section: Discussioncontrasting
confidence: 73%
“…Data from various studies on factors affecting children's CAP incidence were analyzed. A cross-sectional study of 94 children in Pakistan using conventional culture-identified atypical bacteria, viruses, and Mycobacterium pneumonia as etiological agents of pediatric pneumonia [20]. Risk factors for children's pneumonia in Ethiopia included older mothers, housewives, lack of a separate kitchen, recent acute lower respiratory tract infections, and parental asthma [21].…”
Section: Analysis Of Studies On Risk Factorsmentioning
confidence: 99%